Analysis of Anxiety, Stress, Depression and Quality of Life Levels in Elderly Parents with Chronic Diseases - Vivi Sovianti; Endhah Yuliana; M. Nur Kharistna Al Jihad; Prita Adisty Handayani (Indonesian Journal of Global Health Research, 2025)
As the age increases, the elderly are more susceptible to various health problems, one of which is chronic disease. Elderly with chronic diseases who experience excessive stress and anxiety will trigger symptoms of depression so that there is a delay in treatment. This condition can affect the quality of life in the elderly. This study aims to determine the Signs of Anxiety, Stress, Depression and Quality of Life in the Elderly at SMC Telogorejo Semarang. The design of this study is quantitative research and uses a descriptive study design with a cross-sectional approach, the population in this study was 243 elderly, the sample obtained was 71 respondents according to the inclusion and exclusion criteria. The sampling technique used was purposive sampling. The instrument used was DASS (Depresion Anxiety Stress Scale) with Alpha Cronbach table 0.092 and WHOQOL-BREF with Alpha Cronbach coefficient obtained results of 0.882 so that this questionnaire was declared valid and reliable. In the study, the research subjects consisted of 34 men (47.9%) and 37 women (52.1%). respondents aged 60-74 years old elderly 61 respondents (85.9%). Marital status obtained the highest results, namely married 62 respondents (87.3%). Secondary education level as many as 45 respondents (63.4%). Most of the elderly are unemployed as many as 41 respondents (57.7%). In chronic diseases, the majority of diabetes mellitus results were obtained as many as 27 respondents (38.0%). The majority of the elderly experience moderate anxiety (49.3%), moderate stress (49.3%), mild depression (46.5%), the majority of quality of life is sufficient (56.3%).